Antibody Levels to Recombinant Tick Calreticulin Increase in Humans after Exposure to Ixodes scapularis (Say) and Are Correlated with Tick Engorgement Indices - Sanders, Martin L.; Glass, Gregory E.; Nadelman, Robert B.; Wormser, Gary P.; Scott, Alan L.; Raha, Syamal; Ritchie, Bruce C.; Jaworski, Deborah C.; Schwartz, Brian S. (American journal of epidemiology, 1999)
The antibody responses of subjects who presented with a definite Ixodes scapularis (Say) tick bite were measured to determine the utility of the antibody response against recombinant tick calreticulin (rTC) as a biologic marker of tick exposure. Subjects bitten by l. scapularis evidenced an increase in anti-rTC antibody levels between visit 1 and visit 2 from 24.3 to 27.1 ng/μ serum (r = 88, p = 0.003), and levels remained elevated at visit 3 (p = 0.005). These anti-rTC antibody levels during visits 2 and 3 were significantly higher than those in four non-exposed controls. Tick engorgement indices, measured on the biting ticks, were found to be correlated with anti-rTC antibody levels (e.g., for visit 3: Pearson's r= 0.357, p = 0.001). Tick engorgement index (TEI), ratio of body length to scutal width, was identified to be the only independent predictor of anti-rTC antibody levels in linear regression models. Logistic regression revealed that a bite from an l scapularis tick that became engorged (TEI >3.4) was a risk factor for anti-rTC antibody seropositivity (adjusted odds ratio for age and bite location = 7.4 (95% confidence interval 2.1–26.4)). The anti-rTC antibody test had a sensitivity of 0.50 and a specificity of 0.86 for a bite from l. scapularis that became engorged. Immunoblotting revealed that subjects made a specific anti-rTC antibody response. Am J Epidemiol 1999; 149: 777–84.